“You treat your stress by doing what you’re supposed to do”: a qualitative inquiry into emotion regulation of paramedics and paramedic students in critical incidents - Branislav Uhrecký; Veronika Kučerová; Denisa Paksi (BMC Emergency Medicine)
Abstract Background Emergency medical services (EMS) are among the professions with a high degree of responsibility and the frequency of critical situations. Existing research is largely quantitative and provides little insight into the specifics of critical incidents and the emotion regulation strategies used to manage them. Furthermore, little is known about the process by which an experienced paramedic is equipped with emotion regulation resources in the profession. Method In this study, we interviewed 12 experienced paramedics (at least 4 years of practice) and 10 urgent medical care students about the most intense acute stressors they encounter and the emotion regulation that these stressors trigger. Results Psychological distancing, attention management, cognitive framing and interpersonal self-regulation were used by both groups as means of emotion regulation. Identification with the professional role is a key aspect of maintaining a sense of psychological distance. A balance between distance and connectedness is sought. It is not so easy for paramedic trainees to achieve a sense of psychological distance from patients and relatives, and their attention may shift from the situation to themselves, leading to greater anxiety. Conclusion Emotions and emotion regulation are taboo subjects in paramedic community, but greater awareness of them might be beneficial in psychological adaptation to work.